A review of black seed extract as an agent in the wound healing process - Mohd Zaid, Muhammad Hakeem; Hanafi, Muhammad Faezuddin; Haris @ Harith, Muhammad Salahuddin (IIUM Press, 2021)
Introduction: Nigella Sativa or Black Cumin is an annual flowering plant that can be used for wound treatment. In the treatment for wound healing, this plant contains many beneficial components that can help with the treatment but this plant utilisation in the medical field is still limited. This review will provide an overview of the advantages when this plant is used in the wound healing treatment. Method: The review was based on the ROSES protocol, and the databases used were ScienceDirect, PubMed, and Google Scholar. After the search, only 11 papers had been chosen to be included in the results and they were divided into four main themes that were used for the analysis of the results. Results: The themes were gross analysis, microscopic analysis, biochemical analysis and antimicrobial analysis. Conclusion: In conclusion, the black seed extract contains several valuable properties, such as antimicrobial and antioxidant properties, which help improve the wound healing process. Further study needs to be done to discover more potential of Nigella Sativa in treating the wound.